2014
DOI: 10.1111/1346-8138.12364
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of matrix‐assisted laser desorption and ionization time‐of‐flight mass spectrometry for identification of infantile seborrheic dermatitis‐causing Malassezia and incidence of culture‐based cutaneous Malassezia microbiota of 1‐month‐old infants

Abstract: Matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF-MS) has been utilized for identification of various microorganisms. Malassezia species, including Malassezia restricta, which is associated with seborrheic dermatitis, has been difficult to identify by traditional means. This study was performed to develop a system for identification of Malassezia species with MALDI-TOF-MS and to investigate the incidence and variety of cutaneous Malassezia microbiota of 1-month-old inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…These results differ from those published by Kolecka et al (24), who succeeded in building a MALDI-TOF database for identifying Malassezia yeasts from strains cultivated on Dixon medium, possibly due to the use of another mass spectrometer. A second Malassezia database built and tested by another group (25) was obtained from cultures grown on CHROMagar Malassezia medium, which contains glycerol and a low proportion of Tween 60. Furthermore, modification of the quantities of formic acid and acetonitrile during the extraction procedure was revealed to be crucial to obtaining interpretable spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results differ from those published by Kolecka et al (24), who succeeded in building a MALDI-TOF database for identifying Malassezia yeasts from strains cultivated on Dixon medium, possibly due to the use of another mass spectrometer. A second Malassezia database built and tested by another group (25) was obtained from cultures grown on CHROMagar Malassezia medium, which contains glycerol and a low proportion of Tween 60. Furthermore, modification of the quantities of formic acid and acetonitrile during the extraction procedure was revealed to be crucial to obtaining interpretable spectra.…”
Section: Discussionmentioning
confidence: 99%
“…These results are comparable with those of the other two databases published recently. The first, developed by Kolecka et al (24), included 14 species (48 strains) and identified 84.8% of the strains tested, whereas the latter, from Yamamoto et al (25), contained 8 species (18 strains) and identified 92.8% of the unknown strains with a log score value between 1.7 and 2.0. Although our database currently contains only six species, it remains representative of the local epidemiology of Malassezia yeasts in France.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, the non-uniformity in the culture media used may be another important issue when interpreting the results. 30,35 Susceptibility profile and treatment Therapy of Malassezia bloodstream infections is mainly based on previous experience and antifungal susceptibility data. Susceptibility testing has not been standardized for these yeasts and therefore is not performed by routine in many clinical laboratories.…”
Section: Diagnosismentioning
confidence: 99%
“…Recently, matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF‐MS), mainly developed by Japanese engineers, has become the state‐of‐the‐art procedure in medical or biological research. Several studies demonstrated the value of MALDI‐TOF‐MS as an intensive identification system for Malassezia isolates …”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the value of MALDI-TOF-MS as an intensive identification system for Malassezia isolates. 13,14 Since the early 2000s, the culture-independent and PCRbased methods described above have been employed for analyses of the human microbiota of microorganisms including viruses, bacteria and fungi. [15][16][17] Moreover, these methods enabled direct detection of the Malassezia microbiota in normal skin as well as in lesional skin of PV, SD or AD patients.…”
Section: Introductionmentioning
confidence: 99%